FAKTOR KOMUNIKASI DAN SIKAP YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PAJAK BUMI DAN BANGUNAN DI KECAMATAN PARANG KABUPATEN MAGETAN - WAHYU WIDHAWAN, DHORES Wahyu (Jurnal Akuntansi AKUNESA, 2013)
Purpose of this research is focused on several factor that can influence implementation policy Land Building and Tax’s policy in  Parang, Magetan, covers factor of attitude and communication. This object of research is tax service office in Parang. This research is using analysis qualitative method and using Van Metter and Van Horn’s model theory. The result of this research is implementation policy land building and high low of tax’s revenue in Parang is influenced by  attitude and communation factors. Keyword : land building tax, attitude, communication